Dynamics Simulation and Experiment of the Slider-crank Mechanism with Dry Friction Clearance Joint - Han Yuncheng; Xu Lixin; Huang Xiaoqiu (Jixie chuandong)
Based on dynamics simulation software,the dynamics analysis of the slider-crank mechanism with clearance joint is carried out and the effect of joint with different clearance size under dry contact and non-friction conditions on dynamic response of slider-crank mechanism is researched. A slider-crank mechanism test rig is built,through experimental,the effect of joint with different clearance size under dry contact and fully lubricated conditions on dynamic response of slider-crank mechanism is researched. The studies show that joint with clearance lubricated or not,clearance size and speed have an impact on the dynamic response of slider-crack mechanism.